Migration of biogenic substances through the aeration zone - Litvinaitis, Andrius; Bagdžiūnaitė-Litvinaitienė, Lina (International Conference “Environmental Engineering”, 2023)
The article presents the migration of biogenic substances in the aeration zones of different sedimentary riverbanks. Sand and loam sediments in Lithuanian river basins are studied, and experimental research is carried out under natural conditions by increasing the loads of biogenic substances. The modeling was performed using the modeling program CHMFLO-2000. It was established that the transport of total nitrogen by the river water is formed by the amounts of nitrates, which make up 92–97% of the total transport in individual seasons. Nitrates account for 15–23% of the total nitrogen transport through sediment surface and groundwater runoff. The regularities of vertical and horizontal migration of biogenic substances have been established and defined. The suitability of the modeling program CHEMFLO-2000 for modeling the transport processes of ammonium ions, nitrates and nitrites by underground runoff on the banks of Lithuanian rivers has been confirmed, the applicable constants for modeling have been provided.
Keywords: aeration zone; biogens; modelling; ground water; river pollution